Prohexadione Calcium Improves Rice Yield Under Salt Stress by Regulating Source–Sink Relationships During the Filling Period - Rui Deng; Dianfeng Zheng; Naijie Feng; Aaqil Khan; Jianqin Zhang; Zhiyuan Sun; Jiahuan Li; Jian Xiong; Linchong Ding; Xiaohui Yang; Zihui Huang; Yuecen Liao (Plants, 2025)
Salt stress is an important factor affecting the growth and development of rice, and prohexadione calcium (Pro-Ca) plays an important role in alleviating rice salt stress and improving rice yield. However, there are few studies on how Pro-Ca improves rice yield under salt stress by regulating the source–sink metabolism. In this study, we used Guanghong 3 (salt-tolerant variety) and Huanghuazhan (salt-sensitive variety) as experimental materials to investigate the dynamic changes in the synthesis and partitioning of nonstructural carbohydrates among source–sink, the dynamic changes in related enzyme activities, the effects of the source–sink metabolism on yield in rice under salt stress and the effect of Pro-Ca during the filling period. The results of this study showed that Pro-Ca improved photosynthetic efficiency by increasing leaf photosynthetic gas exchange parameters and other stomatal factors on the one hand and, on the other hand, promoted sugar catabolism and reduced sugar synthesis by increasing leaf sucrose synthase activity and decreasing sucrose phosphate synthase activity, alleviating the inhibitory effect of high concentrations of sugars in the leaves on photosynthesis. Meanwhile, Pro-Ca promotes the transport of sugars from source (leaves) to sink (seeds), increases the sugar content in the seeds, and promotes starch synthesis in the seeds by increasing starch phosphorylase, which promotes seed filling, thus increasing the number of solid grains on the primary and secondary branches of the panicle in rice, increasing the 1000-grain weight, and ultimately increasing the seed setting rate and yield. These results indicated that Pro-Ca alleviated the inhibitory effect of salt stress on rice leaf photosynthesis through stomatal and non-stomatal factors. Meanwhile, Pro-Ca promotes the transport of rice sugars from source to sink under salt stress, regulates the source–sink relationship during the filling period of rice, promotes starch synthesis, and ultimately improves rice yield.